2012
DOI: 10.3892/etm.2012.872
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical factors affecting the selection of an operative approach for fibular fractures involving the posterior malleolus

Abstract: Several operative approaches are available at present for the exposure and fixation of distal fibular fractures combined with posterior malleolus fractures. The present study was designed to study the anatomical characteristics of the distal fibula and to thereby evaluate the advantages and limitations of various operative approaches, as well as their indications for specific conditions. Ten leg specimens from below the knee joint were dissected using posterior, lateral and posterolateral approaches to the fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Wang et al . reported that the distance was 7.2 ± 4.1 mm between the sural nerve and the posterior section of the fibula [ 26 ]. The surgeon must be aware that the anatomy of the sural nerve is highly variable and the best way to protect it and avoid nerve injury and neuromas is to perform meticulous blunt dissection in the subcutaneous tissue.…”
Section: Techniquementioning
confidence: 99%
“…Wang et al . reported that the distance was 7.2 ± 4.1 mm between the sural nerve and the posterior section of the fibula [ 26 ]. The surgeon must be aware that the anatomy of the sural nerve is highly variable and the best way to protect it and avoid nerve injury and neuromas is to perform meticulous blunt dissection in the subcutaneous tissue.…”
Section: Techniquementioning
confidence: 99%